2017
DOI: 10.11648/j.ijhnm.20170305.11
|View full text |Cite
|
Sign up to set email alerts
|

Codon Usage Study on Chloroplast Genome in Medicinal Plant <i>Panax Ginseng</i>

Abstract: Abstract:Panax ginseng is usually used as a famous plant medicine in many countries. In order to study the codon usage in whole chloroplast genome in Panax Ginseng, whole chloroplast genome sequence is analyzed via codonW software and some results such as relationships between the codon adaptation index, frequency of optimal codons, codon bias index, effective number of codons, especially the relative synonymous codon usage are all discussed. Furthermore, PR2-bias plot, histogram GC content, Codon Bias Index a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is a well-known fact that synonymous codons are not used with equal frequencies, which shape the tRNAomes in both eukaryotes and prokaryotes. A statistical analysis of the chloroplast genome in Panax ginseng based on codon count (relative synonymous codon usage, RSCU) indicated that 31 codons in ginseng chloroplast genome with RSCU larger than 1.0 were preferred [22]. However, we surprisingly found that many corresponding anticodons were obviously completely absent in the genome (KF431956.1) or minimally transcribed ( Figure 4C), suggesting a low correlation between the practical codon usage bias and the codon frequencies in genomes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is a well-known fact that synonymous codons are not used with equal frequencies, which shape the tRNAomes in both eukaryotes and prokaryotes. A statistical analysis of the chloroplast genome in Panax ginseng based on codon count (relative synonymous codon usage, RSCU) indicated that 31 codons in ginseng chloroplast genome with RSCU larger than 1.0 were preferred [22]. However, we surprisingly found that many corresponding anticodons were obviously completely absent in the genome (KF431956.1) or minimally transcribed ( Figure 4C), suggesting a low correlation between the practical codon usage bias and the codon frequencies in genomes.…”
Section: Discussionmentioning
confidence: 87%
“…From this sequence data, 25 chloroplastic tRNA isoacceptors were identified by searching against the chloroplast genome of Panax ginseng reported previously, and 16 new tRNAswere also detected by capturing primary and second structure motif of each sequence in the TEF library ( Figure 4C and Table S10). The relative abundance of each tRNA isoacceptor was estimated by read frequency, and the result showed that tRNA transcripts were highly variable in ginseng root, which might be affected by the codon usage bias [22,23]. It is worth noting that some tRNA modifications represent a fundamental hurdle for the reverse transcriptase during cDNA synthesis.…”
Section: Ginseng Trnas Enriching and Sequencingmentioning
confidence: 99%